Analysis of some nonlinear deterministic oscillators using extended averaged equation approach - Hai, Ninh Quang (Vietnam Journal of Mechanics, 2005)
The paper presents an application of extended averaged equation approach in investigating some nonlinear oscillation problems. The main idea of the method is briefly described and numerical simulations are carried out for some nonlinear oscillators. The results in analyzing oscillation systems with strong nonlinearity show advantages of the method.